2014
DOI: 10.33700/1580-7118.16.2.101-126(2014)
|View full text |Cite
|
Sign up to set email alerts
|

Where Do Immigrant Children Come From and Why?

Abstract: The early 21st century continues the trend from the later 20th century: the first-generation immigrant children who move to Slovenia most often come from the states established after the disintegration of former Yugoslavia – from Bosnia and Herzegovina, Kosovo, Macedonia, as well as from Serbia, Croatia and Montenegro. There are few arrivals from other states and continents, such as Bulgaria, Ukraine, or the United States of America. This article presents certain experiences that vary for each immigrant family… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Many students in Slovenia with an immigrant background belong to the ethnicities of the countries of former Yugoslavia. In most cases, these students and/or their parents are economic migrants and/or refugees who came to Slovenia during the war in the Balkans and then remained (Ribičič, 2004;Vižintin, 2014). In recent years, however, the number of refugees coming to Slovenia from the Middle East (EMN, 2017) has been growing as well.…”
Section: Students With An Immigrant Background In the Slovenian Educational Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Many students in Slovenia with an immigrant background belong to the ethnicities of the countries of former Yugoslavia. In most cases, these students and/or their parents are economic migrants and/or refugees who came to Slovenia during the war in the Balkans and then remained (Ribičič, 2004;Vižintin, 2014). In recent years, however, the number of refugees coming to Slovenia from the Middle East (EMN, 2017) has been growing as well.…”
Section: Students With An Immigrant Background In the Slovenian Educational Environmentmentioning
confidence: 99%
“…It can be seen that even if Slovenia's educational environment does provide equal rights and language learning and learning support to firstgene ration immigrant students, it is lagging behind in successful inclusion and in providing equal opportunities for all students with an immigrant background. It can also be observed that intercultural dialogue in the school environment between the majority population and immigrant students is missing (Vižintin, 2014(Vižintin, , 2017. With high levels of discrimination, the social environment does not favour students with an immigrant background and only permits the expression of a non-native ethnic identity in the private sphere of an individual's life.…”
Section: Students With An Immigrant Background In the Slovenian Educational Environmentmentioning
confidence: 99%
“…Many students in Slovenia with an immigrant background belong to the ethnicities of the countries of former Yugoslavia. In most cases, these students and/or their parents are economic migrants and/or refugees who came to Slovenia during the war in the Balkans and then remained (Ribičič, 2004;Vižintin, 2014). In recent years, however, the number of refugees coming to Slovenia from the Middle East (EMN, 2017) has been growing as well.…”
Section: Students With An Immigrant Background In the Slovenian Educational Environmentmentioning
confidence: 99%
“…It can be seen that even if Slovenia's educational environment does provide equal rights and language learning and learning support to firstgene ration immigrant students, it is lagging behind in successful inclusion and in providing equal opportunities for all students with an immigrant background. It can also be observed that intercultural dialogue in the school environment between the majority population and immigrant students is missing (Vižintin, 2014(Vižintin, , 2017. With high levels of discrimination, the social environment does not favour students with an immigrant background and only permits the expression of a non-native ethnic identity in the private sphere of an individual's life.…”
Section: Students With An Immigrant Background In the Slovenian Educational Environmentmentioning
confidence: 99%